Eastern Shoshone and Northern Arapaho Traditional Ecological Knowledge (TEK) and Ethnobotany for Wind River Reservation Rangelands - Colleen Friday; John Derek Scasta (Ethnobiology Letters, 2020)
The need to affirm and revitalize cultural knowledge of native plant communities is impera-tive for Indigenous people. This ethnobotanical study documents Traditional Ecological Knowledge (TEK) structured from an Indigenous paradigm by exploring the connection be-tween plants collected in two high-elevation basins and tribal members on the Wind River Indian Reservation (WRIR). We sought to qualitatively understand the plant resources by looking through the lens of Indigenous language and perspectives. Existing names of the ba-sin plants in both the Eastern Shoshone and Northern Arapaho languages were compiled through an ethnobotanical literature review, seven in-person interviews with Eastern Sho-shone and Northern Arapaho tribal members, and attendance at language workshops. We documented 53 Eastern Shoshone and 44 Northern Arapaho plant names, respectively. His-torical impacts of past Federal Indian policy eras have shaped TEK as it currently exists within tribal communities. Both tribes used and had Indigenous names for Northern sweetgrass (Hierochloe hirta ssp. hirta), bitterroot (Lewisia rediviva), junipers (Juniperus ssp.), and bear-berry or Kinnikinnick (Arctostaphylos uva-ursi). The resiliency of TEK is attributed to the perse-verance of Indigenous people continuing to practice and teach traditions. The historical con-text specific to both the Eastern Shoshone and Northern Arapaho tribes and their languages are important for enhancing our current understanding of the ethnobotanical TEK of plants on the WRIR. Recognizing the value of ethnobotanical TEK and incorporating it into natural resource management plans and decisions can bridge diverse perspectives on land use for meaningful collaboration with tribal communities.